Edge AI Solution for Securing and Monitoring of Retail Property - Saci Wissam Semama Sara (univercity of eloued جامعة الوادي, 2023)
The massive development in Artificial Intelligence (AI) and the growing demand for effective security systems have led to the development of smart solutions suitable for securing and monitoring retail properties. This master’s thesis presents the design, development, and evaluation of a deep learning-based model that has a specific focus on real-time detection of abnormal behavior in retail environments. The proposed solution takes advantage of the computing capabilities of end devices to process video streams locally, thus reducing reliance on cloud-based infrastructures and enabling faster response times. To achieve this goal, we will prepare a dataset for our project with data from UCF-Crime, which presents a variety of retail scenarios that include many of the anomalous behaviors encountered in real-world retail environments. The proposed model uses the convolutional neural network based on DenseNet-121 as the feature extractor , which is integrated with a detection system developed to capture spatial and temporal signals from video data. Le développement massif de l’intelligence artificielle (IA) et la demande croissante de systèmes de sécurité efficaces ont conduit au développement de solutions intelligentes adaptées à la sécurisation et à la surveillance des propriétés commerciales. Ce mémoire de master aborde la conception, le développement et l’évaluation d’un modèle basé sur l’apprentissage profond qui se concentre sur la détection en temps réel des comportements anormaux dans les environnements de vente au détail. La solution proposée tire parti des capacités informatiques des terminaux pour traiter les flux vidéo localement, réduisant ainsi la dépendance aux infrastructures basées sur le cloud et permettant des temps de réponse plus rapides. Pour atteindre cet objectif, nous allons préparer un ensemble de données pour notre projet avec des données d’UCF-Crime, qui présente une variété de scénarios de vente au détail qui incluent de nombreux comportements anormaux rencontrés dans les environnements de vente au détail du monde réel. Le modèle proposé utilise le réseau neuronal convolutif basé sur DenseNet-121 comme extracteur de caractéristiques, qui est intégré à un système de détection développé pour capturer des signaux spatiaux et temporels à partir de données vidéo.
مذكرة ماستر اعلام الي
Keywords: Edge AI; Abnormal behavior; DenseNet-121; UCF-Crime.; IA périphérique; Comportement anormal